From sustainable cities to sustainable people - making behaviour change towards sustainability a priority in urban planning processes. - Stieninger Hurtado, Petra (My University, 2018)
For many years, cities across the globe have developed sustainability strategies, trying to combat environmental pollution and its effects on climate change, health, and quality of life. Even though most of them are following similar strategies, not every city is successful. The discussion about urban sustainability mainly focuses on technical solutions such as public transportation systems, green buildings, and the use of renewable energy. However, most cities don't take into consideration that the main factors that make a city sustainable are the people who live in it. Sustainability is not just about using new technologies to make cities and their systems more sustainable by addressing the technical causes of inefficiencies. Sustainability is about changing behavior of people by addressing the root causes of unsustainable behavior. Building public transportation systems and bike lanes doesn't guarantee that people will use them and drive less. To create a sustainable city, planners have to address the factors that encourage people to choose the sustainable option over the unsustainable one. Hence, urban planning must be about creating an environment that allows and motivates sustainable behavior. The main findings of this work are five factors that can make a change towards sustainable behavior possible when incorporated into the planning process: availability, accessibility, affordability, attractiveness, and awareness of sustainable options (the five A Planning Approach). The paper outlines these five factors and explains how they can be integrated in urban planning processes in order to enable long-term behavior change towards sustainability.
Keywords: Nachhaltige Stadtentwicklung; Umweltpsychologie; Verhaltensänderung